Északnyugat-Dunántúl gazdasági és ipari szerkezetének átalakulása - Máthé, Mária (Tér és Társadalom, 1997)
The study attempts to briefly analyse those groups of factors through which the transition process of the Hungarian economy and industry can be examined. As a result of this process, some initial phases of the core regions of the regional organisations, similar to the market economy districts of the developed countries, can be seen. In this process both local and regional governments and the State government played an important role. The process was extremely difficult, as practically the whole of this pioneer process took place without any prior experiences and samples. It went with only one deficiency, or "Scarlet Letter": It almost completely lacked Hungarian capital. Among the foreign investors there was a number of soldiers of fortune, and foreign capital which arrived with speculation purposes, which pollutes the environment and pays unfairly low wages still persists. Given the experiences of the transformation process, we can clearly define those instruments – economic, regional and industrial development strategy of the government, regional influencing factors, e.g. large businesses, local and regional power – the knowledge of which is necessary for either the local or the regional levei of administration to intervene in the development processes. Furthermore, we can also clearly define those endowments in the Nortwest Transdanubian region which can be the bases of an innovation-oriented regional economy that is built on economic clusters. From the applied tools, the available state resources play an important role because the expectations of the State’s will can be asserted through them, until a certain size of the businesses, of course. As a summary we can say that the complex processes amounted to the strengthening and capital concentration of the foreign, private owned large businesses in Nortwest Transdanubia and maybe at Hungarian levei too, at the same time several newly established small and medium size enterprises went bankrupt. However, if the drop in the foreign share in the capital assets is the consequence of the withdrawal of the speculation capital – i.e. the capital that is not integrated into the regional economy – from Hungary, then a positive process has started which will probably result in the appearance of industrial and economic districts which provide a stable living and development for the region.